Water scarcity and alternative water sources in South Africa: can information provision shift perceptions? - Prinsa, F.X.; Etale, A.; Ablo, A.D.; Thatcher, A. (Taylor & Francis Group, 2022)
Consumer perceptions are key to the success of strategies to address water scarcity. A decision pathway survey was used to investigate attitudes amongst South Africans (N = 668) in urban areas towards four alternative water sources. Results showed that storm and rainwater harvesting was the most (49.7%), and reclaimed wastewater the least acceptable options (15.7%). Direct potable reuse was the most supported alternative (26.6%), followed by indirect potable reuse (22.2%), reuse with additional piping (18.3%), direct non-potable reuse (8.3%), and indirect non-potable reuse (6.8%). Importantly, information provision led to a >66% increase in reclaimed wastewater acceptance amongst those initially opposed to it. In contrast, support for desalinated water and water restrictions decreased. Information provision also led to greater acceptance for direct relative to indirect reuse in situations of severe water scarcity. Together, the data suggest a role for information in influencing attitudes towards alternative water sources amongst consumers.
Research Article
Keywords: Recycled water; water reclamation; water reuse; day-zero; sustainability